Analysis of Educational Administration Programs in Doctoral Granting Institutions - Flanigan, J. L.; Richardson, M. D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Findings of a study that analyzed the characteristics of educational administration programs in doctoral granting institutions are presented in this paper. Questionnaires mailed to the department of educational administration chairpersons at 40 universities in the south central United States yielded 28 responses. Slightly over half of the respondents (15) reported the enrollment of 10 or fewer full-time doctoral students. A great disparity was found in the ratios of full-time staff to doctoral students. No clearly defined methods existed for distinguishing the overlap between department of educational administration faculty positions and other departments. Departments lacked a common area of faculty expertise, which raises the question of whether educational administration programs resulted from program direction or from individual faculty members' expertise. Eight tables and one figure are included. (2 references) (LMI)
ERIC Note: Paper presented at the Annual Meeting of the Society of Professors of Education (San Francisco, CA, April 20-24, 1992).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; College Programs; Doctor of Arts Degrees; Doctoral Degrees; Doctoral Programs; Educational Administration; Graduate School Faculty; Graduate Study; Higher Education; United States (Southeast); Speeches/Meeting Papers; Reports, Research